Wirausaha Inovasi Produk Puding Ubi Unggu Dengan Penambahan Vla Gula Merah - Yuti Anita; Vineza Elsafa; Naufal Aziz Alfikri; Jejen Pratama Saputra; Wahyu Sucipto; Eko Sumartono (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The entrepreneurial activity of product ivonation "Purple Sweet Potato Pudding with the Addition of Brown Sugar Vla" was carried out in November and December 2023 at Dehasen University Bengkulu, aiming to analyze the feasibility of the business, production costs of income and profits from the product ivonation. By utilizing local foods in the Bengkulu region such as purple sweet potatoes and palm sugar.  Product innovation is carried out by students of the Agricultural Product Technology Study Program, Faculty of Agriculture, Dehasen University Bengkulu. This activity was carried out by direct marketing method at the bazaar activity carried out by Dehasen University Bengkulu. After analyzing the data, it is hoped that the product innovation of Ubi Unggu Pudding with the Addition of Brown Sugar can become a viable entrepreneurial endeavor.